Features liable for illegally obtaining and disclosure of information constituting a trade secret. (Journal of actual problems of jurisprudence, 2016)
Article is devoted to the concepts and types of responsibility for illegally obtaining and disclosure of information constituting a trade secret, the specifics of determining the grounds for liability for illegally obtaining and disclosure of information constituting a trade secret.
Keywords: liability; trade secrets; commercial information; undisclosed information